2019
DOI: 10.1089/neu.2018.6157
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Neurophysiological Dynamics in Traumatic Brain Injury: Role of Pressure Reactivity and Optimal Cerebral Perfusion Pressure for Predicting Outcome

Abstract: Intracranial pressure (ICP), cerebral perfusion pressure (CPP), and the pressure reactivity index (PRx) have been shown to correlate with outcome after traumatic brain injury (TBI), but their temporal evolution is less studied. Optimal CPP (CPPopt; i.e., the CPP with the lowest [optimal] PRx value) has been proposed as a dynamic, individualized CPP target. Our aim was to map the temporal course of these parameters and their relation to outcome, in particular the extent and impact of CPP insults based both on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 33 publications
3
62
2
Order By: Relevance
“…We have also found that ICPV defined as the absolute deviation from the mean value for 4 h was significantly higher for those with favorable compared to unfavorable outcome [5].…”
Section: Icpv: Different Time Intervals and Relation To Outcomesupporting
confidence: 58%
See 3 more Smart Citations
“…We have also found that ICPV defined as the absolute deviation from the mean value for 4 h was significantly higher for those with favorable compared to unfavorable outcome [5].…”
Section: Icpv: Different Time Intervals and Relation To Outcomesupporting
confidence: 58%
“…A previous study found that the pressure reactivity index was best evaluated in the frequency range with oscillations with periods from 55 to 15 s (PRx55-15) [5,12]. Similarly, ICP AMP 55-15 was an independent predictor of outcome, but ICPV-30m was a slightly stronger outcome predictor (Table 3).…”
Section: Icpv: Different Time Intervals and Relation To Outcomementioning
confidence: 87%
See 2 more Smart Citations
“…30 Pressure reactivity index, traditionally calculated as the 5-minute correlation of 10-second averages of ICP and MAP, 31 was used in combination with a bandpass filter, limiting the analysis to oscillations with periods of 15 to 55 seconds (PRx55-15). 32,33 For MD, we used the 71 High Cut-Off Brain Microdialysis Catheter with a membrane length of 10 mm and a membrane cutoff of 100 kDa (M Dialysis). The MD catheter was placed in normal-appearing brain tissue in the right frontal lobe, adjacent to the ICP monitor.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%